PELATIHAN PENINGKATAN PEMAHAMAN MASYARAKAT TERHADAP ASPEK HUKUM TINDAKAN BULLYING/PERUNDUNGAN - Husna, Lenny; Nurma Dhona Handayani; Ukas, Ukas; Arman, Zuhdi (ASOSIASI IDEBAHASA KEPRI, 2024)
Bullying is an action that is not new and occurs in society, especially among teenagers. In the past, we often used the term